The knowledge and attitudes of students about human papillomavirus and HPV vaccine - Antić Ljiljana; Antić Dragan; Aleksopulos Hristos; Despotović Mile; Zlatanović Milena (Association of Nurses Technicians and Midwives, 2018)
INTRODUCTION: Human papillomavirus (HPV) represents a huge health issue, not only with us, but worldwide as well, considering that HPV is the trigger of the cervical cancer and one of the most common infections transmitted through sexual contact. This implies that students of vocational studies poses an adequate knowledge about the risk factors, prevention and diagnosis of this severe illness. AIM: The aim of this research is to look into the diﬀerences of the knowledge and attitudes of the students about HPV as the cause of the cervical cancer, and to apply HPV vaccines in pre-testing and post-testing. METHODS: The research includes 104 students (53 in pre-testing and 51 in post-testing), aged from 19 to 35; 93% female students and 6.5% male students of the College of Applied Health Sciences in Ćuprija. RESULTS: The students demonstrated the best knowledge during the post-testing about the registered HPV vaccines, 83.9% of students in comparison to 5.7% during the pre-testing (p<0.000). The students had a high knowledge level in post-testing (68.5% of students) about the target population for HPV vaccine, in comparison to 32.1% of students during pre-testing (p<0.000). Surprisingly, the students demonstrated less knowledge about the cervical cancer prevention during post-testing (64.7%), in contrast to pre-testing, where 71% of students answered correctly (p=0.005). CONCLUSION: The knowledge of the students about HPV and HPV vaccine during pre-testing is considered unsatisfactory. The knowledge that the students demonstrated in post-testing may be satisfactory, whereas the level of awareness about prevention has not been higher in post-testing either.